Analisis Preferensi Konsumen Pada Gula Kelapa Di Kecamatan Way Jepara Kabupaten Lampung Timur (Studi Kasus Di Pasar Way Jepara) - Wintari Mandala; Novia Ambar Sari (KaliAgri Journal, 2023)
Sugar is one of the national strategic food commodities. National demand for sugar will increase in line with the increase in population, people's income and the growth of the food and beverage processing industry. Palm sugar is sugar made from coconut sap through the process of filtering coconut sap water, heating it and then molding it.The purpose of this study is to determine consumer preferences for palm sugar products and the attributes most preferred by consumers. The method used is survey method. Purposive location etermination. Respondents were determined by simple random sampling. Data analysis using Conjoint Analysis. The results of research on consumer preferences are that they prefer the color of palm sugar to dark brown-black, the taste of sugar is very sweet, the size of palm sugar is large, the packaging of leaves and the price is not too high or expensive.